Avaliação do transporte de sedimentos na ruptura de barragens de rejeito - Bruna Carolina de Melo Almeida (2022)
Mining is one of the main economic sources in Brazil. Tailings are found as a by-product of all mining activities, and those materials carry no significant added economic value. Its disposal, most often carried out in dams, must be based on solutions that combine the minimization of environmental impacts associated with the lowest cost for its containment and security. The occurrence of the rupture of tailings dams is a catastrophic event, which causes several environmental and social damages, as it was the case of the rupture of the “Fundão” Dam, located in the Municipality of Mariana, in Minas Gerais, Brazil. This rupture occurred on November 5, 2015, leading to a propagation of about 32 million m³ of tailings through the downstream valley, causing the destruction of Bento Rodrigues and environmental damage that extended to the river mouth of the “Rio Doce” into the sea, in Regência (ES). One of the instruments that make it possible in advance to assess the possible impacts resulting from a dam failure are the Dam Break studies. Their aim is to carry out a hydrodynamic modeling of a potential flood associated with the eventual rupture of a given structure. One of the aspects related to Dam Break studies that are commonly not considered is related to the transport of sediments caused by the rupture, due to the complexity of establishing a representative equation for the phenomenon. In this present study, it was sought to evaluate the impact of considering this aspect in studies of Dam Break of a tailings dam, using the “Fundão” Dam as a case study. The work methodology was essentially based on the construction of a two-dimensional hydrodynamic model in the HEC-RAS for the study of a hypothetical rupture of the dam, in two different scenarios: with and without considering the transport of sediments. From the analysis of the flood spread along the downstream valley, together with the evaluation of changes in parameters such as speed, maximum depth and wave arrival time, as well as the comparison of the generated flood maps, it was possible to quantify differences in the incorporation of transport of sediments in the simulation of dam ruptures. The use of this tool demonstrates satisfactory results and indicate that the region corresponds to the “Self-Rescue Zone” (ZAS) in the first kilometers downstream from the structure. The consideration or not of the insertion of sediment transport does not result in significant differences in the evaluated parameters.